Measurement of angular correlations of jets at s=1.96 TeV and determination of the strong coupling at high momentum transfers - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Askew, A.; Atkins, S.; Augsten, K.; et al. (Elsevier, 2012)
We present a measurement of the average value of a new observable at hadron colliders that is sensitive to QCD dynamics and to the strong coupling constant, while being only weakly sensitive to parton distribution functions. The observable measures the angular correlations of jets and is defined as the number of neighboring jets above a given transverse momentum threshold which accompany a given jet within a given distance δR in the plane of rapidity and azimuthal angle. The ensemble average over all jets in an inclusive jet sample is measured and the results are presented as a function of transverse momentum of the inclusive jets, in different regions of δR and for different transverse momentum requirements for the neighboring jets. The measurement is based on a data set corresponding to an integrated luminosity of 0.7 fb -1 collected with the D0 detector at the Fermilab Tevatron Collider in pp- collisions at s=1.96 TeV. The results are well described by a perturbative QCD calculation in next-to-leading order in the strong coupling constant, corrected for non-perturbative effects. From these results, we extract the strong coupling and test the QCD predictions for its running over a range of momentum transfers of 50-400 GeV. © 2012 Elsevier B.V.